2012
DOI: 10.5402/2012/649746
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Removal of Endotoxins: A Bioprocess Engineer's Perspective

Abstract: Gram-negative bacteria are widely used for the production of gene-based products such as DNA vaccines and bio-drugs, where endotoxin contamination can occur at any point within the process and its removal is of great concern. In this article, we review the structures of endotoxin and the effects that it causes in vivo. The endotoxin removal strategies are also discussed in the light of the different interaction mechanisms involved between endotoxins and bioproducts particularly plasmid DNA and proteins. For mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 59 publications
(148 reference statements)
0
22
0
Order By: Relevance
“…Quartz discs were systematically handled with thoroughly pre-cleaned stainless steel tweezers to avoid external contamination. Due to endotoxin's ubiquity (Petsch and Anspach, 2000;Ongkudon et al, 2012;Binding et al, 2004), immobilization of PMB (sulfate salt powder from Sigma-Aldrich) was imperatively carried out in sterilized glassware, baked overnight in an oven maintained at 200°C (Petsch and Anspach, 2000), using sterile laboratory equipment and Dulbecco's phosphate buffered saline (PBS, CaCl 2 and MgCl 2 free -pH 7.4, from Sigma-Aldrich) made endotoxin-free (EA ¼0.31) upon filtration through a 0.22 μm syringe driven filter unit. Preparation and handling of PMB-modified quartz discs/glass beads, EMPAS experiments and EA/TNF-α assays were systematically performed in an endotoxin-free environment including sterilized glassware (vide supra) as well as sterile laboratory equipment and solvents/chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…Quartz discs were systematically handled with thoroughly pre-cleaned stainless steel tweezers to avoid external contamination. Due to endotoxin's ubiquity (Petsch and Anspach, 2000;Ongkudon et al, 2012;Binding et al, 2004), immobilization of PMB (sulfate salt powder from Sigma-Aldrich) was imperatively carried out in sterilized glassware, baked overnight in an oven maintained at 200°C (Petsch and Anspach, 2000), using sterile laboratory equipment and Dulbecco's phosphate buffered saline (PBS, CaCl 2 and MgCl 2 free -pH 7.4, from Sigma-Aldrich) made endotoxin-free (EA ¼0.31) upon filtration through a 0.22 μm syringe driven filter unit. Preparation and handling of PMB-modified quartz discs/glass beads, EMPAS experiments and EA/TNF-α assays were systematically performed in an endotoxin-free environment including sterilized glassware (vide supra) as well as sterile laboratory equipment and solvents/chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…The protein purity was estimated to be >98% based on 12% sodium dodecylsulfate-polyacrylamide gel electrophoresis analysis. As previously reported, size-exclusion chromatography has been used for separating endo-toxin from proteins and plasmid DNA, 45 so it means that size-exclusion chromatography is an available method that could be applied to eliminate endotoxin. In this study, we further tested the endotoxin in our experimental samples using the tachypleus amebocyte lysate method, as previously reported, 46 and the results showed that the amount of endotoxin in our protein samples is ~3.2 endotoxin unit/mg, which is significantly less than the US Food and Drug Administration requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Having a molecular mass greater than 10 kDa, lipopolysaccharides (LPS) resulting from the biotechnological processes are large molecules, which sediment during the ultracentrifugation step. In the less probable situation when they are still present in the clarified lysate, SEC is a known method for their elimination 33 , 34 , and that is the reason for the lower endotoxin level detected in our NMN sample compared with the HPLC solvents used. Evidently, an even lower endotoxin level can be obtained by using endotoxin free solvents.…”
Section: Discussionmentioning
confidence: 93%